PENGARUH TENAGA KERJA SEKTOR PERTANIAN DAN PENGELUARAN PEMERINTAH SEKTOR PERTANIAN TERHADAP PRODUK DOMESTIK BRUTO SEKTOR PERTANIAN DI INDONESIA - Sayifullah Sayifullah; Emmalian Emmalian (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this research was to determine the influence and significant of labor agriculture sector and government expenditure agriculture sector either individually or together to Gross Domestic Product (GDP) agriculture sector in Indonesia. The method used in this research is Ordinary Least Square (OLS) for the period 1980-2013. The analysis technique used in thisresearch is multiple linear regression testing normality test, the classical assumption (Multicollinearity, heterocedastity, autocorrelation and proceed with the analysis of OLS (Ordinary Least Square). Its become independent variables in this study were labor of agriculture sector and government expenditure of agriculture sector, while the dependent variable is the Gross Domestic Product (GDP) of agriculture sector. From the analysis conducted showed that thevariables of labor in agriculture sector and government expenditure of agriculture sector has a significant influence on the Gross Domestic Product (GDP) of agriculture sector. Labor of agriculture sector influence (+) positive to Gross Domestic Product (GDP) of agriculture sector and government expenditure of agriculture sector influence (+) positive to Gross Domestic Product (GDP) of agriculture sector.